Early Results From the Implementation of a Lung Cancer Screening Program: The Beaumont Health System Experience. (March 2018) - Lanni, Thomas B.; Stevens, Craig; Farah, Michael; Boyer, Andrew; Davis, James; Welsh, Robert; Keena, Daniel; Akhtar, Adil; Mezwa, Duane
Abstract : Purpose: In 2010, a new study published by the National Lung Screening Trial showed a 20% reduction in mortality for those patients screened with low-dose computed topography (CT) versus x-ray. Recently, the Centers of Medicare and Medicaid have agreed to cover this service for those patients who meet the screening criteria. We compare the outcomes and costs associated with developing and implementing a lung cancer screening program. Materials and Methods: One thousand sixty-five patients were screened from January 2014 to December 2014. These patients were screened on a low-dose CT screening protocol throughout Beaumont Health System. The American College of Radiology Lung Imaging Reporting and Data System (Lung-RADS) were used to assign the score for each patient. Screening eligibility criteria were based on the National Comprehensive Cancer Network guidelines. Downstream activity and revenue was determined after initial low-dose CT screening. Results: At 1 year, 20 patients (1.6%) were diagnosed with lung cancer and another 15 patients were diagnosed with another form of cancer after screening. The median age, packs per day, and pack years smoked for all patients was 63, 1.0, and 39.0 years, respectively. Lung-RADS scores for all patients was 18% (1), 24.1% (2), 6.3% (3), and 5.4% (4). The net revenue for all activity after screening was 3.2 million. Conclusions: The establishment of a low-dose CT lung cancer screening program improved the ability to screen patients as demonstrated by the number of patients screened and those diagnosed with a malignancy. These findings were also consistent with the findings from the National Lung Screening Trial study.